An Empirical Study to Identify Consumer Brand Relationships during a Crisis - Bhattacharya, Subhajit; Dalal, Arunava; Bandyopadhyay, Nirmalya (Indian Journal of Marketing, 2023)
Countless businesses exist only to serve the varying demands of the world’s customers, and those consumers find themselves constantly bombarded by an overwhelming selection of goods and brands. The brand distinguishes the company from its rivals and aids consumers in making educated purchasing decisions. However, when faced with a catastrophic event like the COVID-19 outbreak, consumers’ assessment criteria shifted in response to shifting priorities and circumstances. As a result, shoppers are rethinking their brand loyalties and choosing new ones. This article used the brand archetype framework to determine what factors customers value during times of crisis. It also used the brand archetype framework to identify the elements consumers consider important during a crisis. Data were collected from 207 respondents and using the Relative to an Identified Distribution (RIDIT) approach, the top-rated brand elements were identified based on level of importance or agreement. This study will help practitioners incorporate the identified elements into their brand image. Their subsequent actions will help them remain relevant and essential for their consumers, even in challenging situations.